Seeing others how to redefine worth in a divided world - Lamont, Michèle 1957- (Allen Lane, 2023)
"From internationally renowned sociologist Michèle Lamont, a game-changing argument about what we value and why. How do we measure our self-worth? For many of us, it signifies accomplishment, self-reliance, and wealth. Decades of neoliberalism have driven our definition of success. Yet, as we have amassed more achievements, we have been overwhelmed and overworked in a world of growing inequality. Should we start judging others, and ourselves, differently? In this capstone work, acclaimed sociologist Michèle Lamont argues that it is time to move our focus from having to being. We will only heal ourselves by the power of recognition: by rendering others visible and valued. By drawing on nearly forty years of research and interviews, as well as new interviews with Gen Z, change agents, and cultural icons who intentionally practice and promote recognition, she shows how new narratives are essential to shifting our metrics of success to focus on respect and dignity. Seeing Others fills a gaping hole left by recent economic and psychological thinking, with its focus on nudging, grit, and constant striving, offering a powerful, sociological alternative"--Publisher's description
Keywords: Social comparison; Social comparison / Economic aspects; Self-evaluation; Self-evaluation / Economic aspects; Comparaison sociale; Comparaison sociale / Aspect économique; Auto-évaluation; Auto-évaluation / Aspect économique; interviews; Interviews